REVITALISASI ESTETIKA RITUAL MAPPACCI MELALUI PEMBELAJARAN IPS BERBASIS PROYEK SEBAGAI STRATEGI PENGUATAN IDENTITAS BUDAYA SISWA SMA DI KABUPATEN BONE - Andi Masyita Ratsdiana; Fitra Amalia; Hasni; Ahmad Syawaluddin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the revitalization of the aesthetic values of the Mappacci ritual through project-based Social Studies learning as a strategy to strengthen the cultural identity of senior high school students in Bone Regency. This research uses a literature study method by reviewing various scientific sources such as books, journals, and previous research related to the integration of local culture in the learning process. Data analysis was conducted through content analysis to identify concepts, theories, and research findings related to project-based learning and the cultural values contained in the Mappacci ritual within the Bugis community. The results of the study indicate that project-based Social Studies learning can serve as an effective approach to integrating local culture into the learning process. Through project activities such as cultural observation, discussion, and documentation of traditions, students can understand the symbolic meanings as well as the social and cultural values embedded in the Mappacci ritual. In addition to enhancing students' understanding of local culture, this approach can also foster cultural awareness and a sense of pride in regional identity. Therefore, project-based Social Studies learning can be a relevant strategy in supporting the preservation of local culture while strengthening students' cultural identity in the era of globalization.